1998
DOI: 10.1128/mcb.18.3.1660
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Localization of Human DNA Repair Enzyme O6-Methylguanine-DNA Methyltransferase at Active Transcription Sites in Transcription-Repair Coupling of the Mutagenic O6-Methylguanine Lesion

Abstract: DNA lesions that halt RNA polymerase during transcription are preferentially repaired by the nucleotide excision repair pathway. This transcription-coupled repair is initiated by the arrested RNA polymerase at the DNA lesion. However, the mutagenic O 6 -methylguanine (6MG) lesion which is bypassed by RNA polymerase is also preferentially repaired at the transcriptionally active DNA. We report here a plausible explanation for this observation: the human 6MG repair enzyme O 6 -methylguanine-DNA methyltransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Since, others have found a similar mutation spectrum after methylating agent exposure in actively transcribed genes such as hprt with preferential O 6 mG adduct repair on the transcribed strand (Lukash et al, 1991;Dobo et al, 1998) to that which we observed, and plasmid shuttle vector mutation analysis has also yielded similar mutation type changes to those observed here in the presence and absence of AGT (Moriwaki et al, 1991), we conclude that our ®ndings are representative of the impact of AGT on mutation frequency after MNU. This is further supported by the recent ®nding that nuclear localized AGT was present in transcriptionally active regions (Ali et al, 1998), perhaps coupled to nucleotide excision repair (Sitaram et al, 1997). While it is likely that the overall repair of O 6 mG adducts is lower in the inactive lacI gene than in actively transcribed genes, the mutation spectrum and type speci®c frequency di erences between the Big Blue TM and MGMT+/Big Blue TM mice are also likely to be predictive of the changes found in actively transcribed genes.…”
supporting
confidence: 65%
“…Since, others have found a similar mutation spectrum after methylating agent exposure in actively transcribed genes such as hprt with preferential O 6 mG adduct repair on the transcribed strand (Lukash et al, 1991;Dobo et al, 1998) to that which we observed, and plasmid shuttle vector mutation analysis has also yielded similar mutation type changes to those observed here in the presence and absence of AGT (Moriwaki et al, 1991), we conclude that our ®ndings are representative of the impact of AGT on mutation frequency after MNU. This is further supported by the recent ®nding that nuclear localized AGT was present in transcriptionally active regions (Ali et al, 1998), perhaps coupled to nucleotide excision repair (Sitaram et al, 1997). While it is likely that the overall repair of O 6 mG adducts is lower in the inactive lacI gene than in actively transcribed genes, the mutation spectrum and type speci®c frequency di erences between the Big Blue TM and MGMT+/Big Blue TM mice are also likely to be predictive of the changes found in actively transcribed genes.…”
supporting
confidence: 65%
“…Although evidence has been presented for the co-localisation of ATase with nascent RNA, (14) the rate of removal of O Phosphorylation of the protein, resulting in a decrease in activity, has recently been reported. (16) One exception to the general alkyl transfer repair mechanism is the action of the protein on N1-O 6 -ethenoguanine.…”
Section: Mechanism Of Atase Actionmentioning
confidence: 98%
“…First, MGMT as a DNA repair factor is constitutively present at active transcription sites, whereas R-MGMT, as a transcription suppressor (Fig. 6E), appears instantly upon exposure to alkylating agents (2). Second, active MGMT is a component of the CBP/p300-containing complex (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4F) that integrates external signals to activate the transcription activities of nuclear receptors (40,43). Furthermore, CBP/p300 is a histone acetylase (17), which can modify the histone octamer in the nucleosome to poise the DNA for transcription (41) and also expose the DNA to undesirable damage by mutagens (2). Thus, it is strategic for MGMT to be a component of the CBP/p300-containing complex (Fig.…”
Section: Discussionmentioning
confidence: 99%